SOCIAL CONTROL AGAINST ONLINE GAME-ADDICTED TEENSIN PADANG SEURAHET VILLAGE, JOHAN HEROES DISTRICT BARAT ACEH DISTRICT - Lia Muliana; M. Nazaruddin; Alwi Alwi; Ibrahim Chalid; Fajri M. Kasim (Malikussaleh Social and Political Reviews, 2022)
The phenomenon of online game addiction is rife in the current digitalization era, especially among teenagers in Padang Seurahet Village. Variants of online games that are often accessed by teenagers are free-to-fire games or war games. Addiction was observed from the outpouring of time playing online games and the non-conformist behavior of adolescents. In analyzing this social event using a qualitative method with a phenomenological approach. The results show that the aspects that encourage teenagers to become addicted to online games are because teenagers can expand their social networks with fellow gamers (gamers), there is an event menu in the game, often get appreciation or prestige in the form of champion certificates and money, get verbal recognition from gamers throughout Indonesia. , and can compete with teams of other players. The issue of online game addiction requires social control from actors such as parents, society, and the government. Parental social control includes advising, limiting smartphones and playing time, sending teenagers to day, and socializing teenagers who are addicted to online games. Padang Seurahet community control is categorized as still minimal in dealing with teenagers addicted to online games, and weak social control (low control) from the Indonesian Government, Regional Government, and Padang Seurahet Gampong Government. The conclusion of this study is a form of parental control in the form of persuasive control, and internal control is not able to minimize online game addiction due to weak control from external actor.